Berliner Weltliteraturen : Internationale literarische Beziehungen in Ost und West nach dem Mauerbau - Müller-Tamm, Jutta 1963- (De Gruyter, 2021)
This volume uses case studies to present the international literary exchange that took place in and around Berlin in the years directly following the construction of the wall and to show how cultural political activities intensified. The fourteen contributions describe in detail a phase in the development of Berlin in which the divided city took on a pioneering role in the internationalization of literary and cultural activities